The Role of Law No. 17 Year 2003 in Promoting Sustainable Financial Performance of State-Owned Enterprises in Indonesia - Loso Judijanto (West Science Law and Human Rights, 2024)
This study investigates the impact of Law No. 17 Year 2003 on promoting sustainable financial performance among State-Owned Enterprises (SOEs) in Indonesia through a qualitative analysis. Interviews were conducted with 10 key informants, including government officials, SOE executives, and industry experts, and data were analyzed using NVivo software. The analysis revealed insights into regulatory compliance, corporate governance practices, strategic decision-making, and challenges and opportunities facing Indonesian SOEs. Despite regulatory challenges such as inconsistent enforcement and political interference, opportunities for improvement including regulatory reforms, stakeholder engagement, and organizational reforms were identified. The findings highlight the complex dynamics influencing SOE performance and underscore the need for collaborative efforts to enhance transparency, accountability, and competitiveness within Indonesian SOEs.